Valorisation of Mediterranean agro-industrial by-products in pig production as feed and anaerobic co-digestion of slurry - Ferrer, Pablo (Universitat Politècnica de València (UPV), 2022)
Nowadays the sustainability of the pig sector relies on its capability to respond to the increasing demands for livestock products that are arising from population growth, adapting to changes in the economic and policy contexts, and improving its environmental performance through the mitigation of its impact on climate. In this framework, the use of the agroindustrial by-products offers potential alternative raw materials for animal production with a lower associated environmental burden in the form of feedstuffs for livestock, source of bioactive compounds or raw materials useful in bioenergy production. This PhD thesis aims to evaluate the use of Mediterranean agro-industrial by-products as feed ingredients for pigs or co-substrates for biogas production. To fulfil these objectives, four trials were designed and conducted to evaluate the use of olive oil and orange juice industry byproducts in swine nutrition, assessing its nutritional value and the consequences of its inclusion in the diet on animals’ performance and health, final product quality traits and gas emissions associated to the pig slurry. Additionally, one more trial was conducted to evaluate the effect of four agricultural substrates (tomato, pepper, peach and kaki) on the biochemical methane potential (BMP) in anaerobic co-digestion with pig slurry, focusing on the type of substrate and its inclusion level on the final substrate’s mixture. The results presented in this PhD Thesis from the nutritional value assays indicate that the olive cakes and orange pulps tested can be potentially included in pig diets to replace part of the cereals of the diet with associated changes in urine and faeces nutrients excretion that leads to modifications in the potential ammonia and BMP emissions from slurries. Concerning olive cake by-products, the nutritional value assay designed to test the crude (COC) and partially defatted (PDOC) olive cakes showed that olive cakes are appreciable sources of insoluble fibre, but have limited energy value (11.2 and 7.4 MJ/kg DM for COC and PDOC respectively) and a low value as protein source. On the contrary, the dehydrated (DOP) and ensiled sun-dried (ESDOP) orange pulps tested are a relevant energy source (14.2 and 13.2 MJ/kg DM for DOP and ESDOP respectively) with added value in terms of SF concentration. With respect to the in vitro potential ammonia and BMP emissions assays, the byproducts tested led to a decreased N excretion in urine and, in the case of the OC, increased DM excretion in faeces. The ammonia emission per kg of slurry decreased with the inclusion of olive cake and orange pulp, whereas the BMP per animal and per day was negatively affected by the inclusion of olive cake obtaining higher BMP with these by-products. Regarding the performance assays, the PDOC and the DOP may be included in balanced pig diets at rates of up to 120 and 240 g/kg respectively, without negative effects in the case of PDOC and minor effects for DOC on growth performance, body composition and carcass quality traits. Contrary to what was expected, the inclusion of PDOC and DOP did not affect microbial counts nor excreta volume, composition and global gas emission from the slurry. Additionally, beneficial effects on subcutaneous fat were observed with the inclusion of PDOC, improving its oleic acid concentration. The anaerobic co-digestion of agricultural by-products and pig slurry improves the BMP from the mixture compared to only pig slurry anaerobic digestion. Higher BMP values were obtained with increasing addition of agricultural substrate, confirming the better performance of co-digestion systems at adequate inclusion levels. In fact, combinations with tomato, pepper and peach at inclusion level 3 (50% of VS) achieved the highest BMP. This resulted in an increase in BMP of 41% with tomato, 44% with pepper, 28% with peach and 12% with kaki. Vegetables substrates (pepper and tomato) showed higher lipid, protein, lignin and cellulose content than fruit substrates (kaki and peach).